وێنەى هەستى و ژیریى لە شیعرى (سالم)دا ئەم توێژینەوەیە بەشێکە لە تێزی دکتۆرا بە ناونیشانی (بنیاتى وێنەى هونەرى لە شیعرى سالمدا) - محمود, فازیل مجید; احمد, مریوان حمەکریم (Sulaimani Journal for Humanities, 2022)
Art image is an important element and contributes to the structure of poetry, to the extent that poetry cannot be formed without the existence of this element. Poets rely on the creation of artistic images, rely on their feelings, or wisdom; the basis for the creation of their paintings, or at the same time participate in both the element of the feeling and the wisdom. This great importance of the image of emotion and wisdom has made us talk about the poetry of one of the top poets of classical literature at Baban Poetry School, Salemi Sahibqran, and Let's talk and show the ability and invention of this kurdish poet in this field.
Keywords: picture; emotion; wisdom; Salim)